Effective Stress Management Strategies in Corporate Settings: An Empirical Study - M.Kovarthini, F.Josephine Lenta (Journal of Informatics Education and Research, 2025)
This research delves into the effectiveness of diverse stress management strategies within corporate environments, assessing their influence on employee well-being, productivity, and overall organizational performance. The study focuses on mindfulness programs, exercise initiatives, time management training, and organizational support mechanisms. Utilizing a sample of 500 employees from various sectors, the study employs both quantitative and qualitative methodologies, including surveys, interviews, and physiological stress measurements. The findings indicate that a multi-faceted approach, integrating several strategies, is the most effective in reducing stress and enhancing productivity. The study concludes with recommendations for implementing these strategies to cultivate healthier, more productive work environments.